The Effect of Pectin and Agar Ratios on the Chemical Characteristics and Microorganisms of Cavendish Banana (Musa Acuminata) - Kharisma Yulia Safitri; Mukhammad Azkal Asror; Pinctada Putri Pamungkas (Perkumpulan Dosen Muda (PDM) Bengkulu, 2026)
Cavendish banana peel waste has the potential to be developed into a functional food product in the form of sheet jam due to its bioactive compounds such as phenolics and flavonoids. This study aimed to analyze the effect of pectin and agar ratios on the chemical characteristics and microorganisms of Cavendish banana (Musa acuminata) peel sheet jam. A completely randomized design (CRD) with one factor and five treatment levels of pectin : agar ratio was applied, namely P1 (1:0), P2 (2:1), P3 (1:1), P4 (1:2), and P5 (0:1), each replicated three times. Parameters analyzed included antioxidant activity (DPPH method), moisture content (oven method), pH, total acid, and microorganism count (TPC method). Results showed that the hydrocoloid ratio significantly affected antioxidant activity (F = 7.339; p = 0.025) and moisture content (F = 265.83; p = 4.18 × 10⁻¹⁰), but did not significantly affect microorganism count (p = 0.159). pH values ranged from 5.4–5.6 and total acid ranged from 1.28–3.20% across all treatments. Treatment P2 yielded the highest antioxidant activity of 74.61% with a moisture content of 15.46%. Storage duration had a highly significant effect on microbial growth, with the product remaining safe for consumption up to day 2 of storage. The P2 formulation is recommended as the optimal treatment for developing Cavendish banana peel sheet jam as an agroindustrial waste-based functional food.